Physicochemical structure and functional properties of soluble dietary fibers obtained by different modification methods from Mesona chinensis Benth. residue. (July 2022) - Yang, Chaoran; Si, Jingyu; Chen, Yi; Xie, Jianhua; Tian, Shenglan; Cheng, Yanan; Hu, Xiaobo; Yu, Qiang
Graphical abstract: Highlights: The three modification methods significantly improved the yield of SDF. The monosaccharide composition and molecular weight of three SDFs were altered. HE-SDF and HU-SDF have porous microstructure and low crystallinity. The functional properties of HE-SDF and HU-SDF were significantly improved. Abstract: Alkaline hydrogen peroxide (AHP), high-temperature cooking combined with ultrasonic (HTCU) and high-temperature cooking combined with complex enzyme hydrolysis (HTCE) were used to modify soluble dietary fiber (SDF) in Mesona chinensis Benth. residue (MCBR), then the structural and in vitro functional properties of A-SDF, HU-SDF and HE-SDF were investigated. Results showed that the three treatments significantly increased the yield of SDF. Scanning electron microscopy, FT-IR, monosaccharide composition, X-ray diffraction, molecular weight distribution and thermal stability analysis were employed to determine the structural changes. Compared with the control SDF (CK-SDF), HE-SDF and HU-SDF had looser and more porous microstructure, as well as lower crystallinity. In contrast to HE-SDF and HU-SDF, A-SDF exhibited a dense wavy microstructure, and elevated crystallinity and thermal stability. In addition, the monosaccharide composition and molecular weight of HU-SDF, HE-SDF and A-SDF were significantly altered as compared to CK-SDF. Moreover, the functional properties of HE-SDF and HU-SDF, including water holding capacity (WHC), oil holding capacity (OHC), glucose adsorption capacity (GAC), α-amylase activity inhibition ratio (α-AAIR), cholesterol adsorption capacity (CAC) and nitrite ion adsorption capacity (NIAC), were significantly higher than those of CK-SDF. However, the dense structure and high crystallinity of A-SDF resulted in a significantly lower GAC and NIAC than that of CK-SDF, with only WHC and α-AAIR being improved. Overall, this study showed that HTCU and HTCE could be used as ideal modification methods for MCBR SDF, HE-SDF and HU-SDF have potential as functional additives in food.